Komitmen Afektif Manajemen dalam Implementasi Sistem Pengukuran Kinerja - Delia Salsabila; Ningrum Fauziah Yusuf (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2021)
Indications that prove a public organization’s growth can be seen from how effective their services can be. Hence there are performance systems and performance measures to see one of the factors behind the effectiveness of such public service. And as application, the performance measurement for the public organization is done to increase the motivation of the organization's management that does not focus only on its output but the relevance of outcomes that can increase the value of public satisfaction of service accessibility. While many factors affect the implementation of performance measurements, one must be considered is affective commitment of management. Where in this case management is encouraged to continue to make improvements and changes in organizations. Researchers are taking a case study of one government agency of fisheries and east Java province, looking into some of the obstacles based on theory of constraints and how a perctive commitment looks for solutions.